2012
DOI: 10.1038/mt.2012.129
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Survival of the Juvenile Lethal Arginase-deficient Mouse With AAV Gene Therapy

Abstract: Arginase deficiency is characterized by hyperargininemia and infrequent episodes of hyperammonemia. Human patients suffer from neurological impairment with spasticity, loss of ambulation, seizures, and severe mental and growth retardation. In a murine model, onset of the phenotypic abnormality is heralded by weight loss beginning around day 15 with death occurring typically by postnatal day 17 with hyperargininemia and markedly elevated ammonia. The goal of this study was to address the development of a gene t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(88 citation statements)
references
References 23 publications
4
83
0
Order By: Relevance
“…Previous gene therapy studies have demonstrated successful reversal of disease manifestations through either treatment of neonatal mice with a helper-dependent adenoviral vector 24 or with adeno-associated virus-expressing arginase. 36 In the former, the transient nature of expression led to loss of arginase function while in the later, long-term survival without neuropathology was achieved; however, with the loss of episomal adeno-associated virus genomes, the level of arginase expression was low and therefore, the animals remained nitrogen vulnerable. 7 However, these murine studies were able to determine that long-term survival 36 with normal behavior and learning 37 was possible and that only low levels of hepatic arginase activity, as low as 3.5–5%, were necessary to prevent brain injury and/or death from hyperammonemia or hyperargininemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous gene therapy studies have demonstrated successful reversal of disease manifestations through either treatment of neonatal mice with a helper-dependent adenoviral vector 24 or with adeno-associated virus-expressing arginase. 36 In the former, the transient nature of expression led to loss of arginase function while in the later, long-term survival without neuropathology was achieved; however, with the loss of episomal adeno-associated virus genomes, the level of arginase expression was low and therefore, the animals remained nitrogen vulnerable. 7 However, these murine studies were able to determine that long-term survival 36 with normal behavior and learning 37 was possible and that only low levels of hepatic arginase activity, as low as 3.5–5%, were necessary to prevent brain injury and/or death from hyperammonemia or hyperargininemia.…”
Section: Discussionmentioning
confidence: 99%
“…36 In the former, the transient nature of expression led to loss of arginase function while in the later, long-term survival without neuropathology was achieved; however, with the loss of episomal adeno-associated virus genomes, the level of arginase expression was low and therefore, the animals remained nitrogen vulnerable. 7 However, these murine studies were able to determine that long-term survival 36 with normal behavior and learning 37 was possible and that only low levels of hepatic arginase activity, as low as 3.5–5%, were necessary to prevent brain injury and/or death from hyperammonemia or hyperargininemia. 7 Here, we developed a CRISPR/Cas9-based strategy to deliver a codon-optimized version of human arginase 1 into hiPSCs derived from patients with arginase deficiency.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…78 The vector contains the ubiquitously-expressing chicken β-actin promoter/CMV enhancer; however it is unclear if functional protein can be produced in extrahepatic tissues. We have previously described using this vector for reporter gene studies 9 and long-term factor VIII expression using a similar neonatal approach in the murine model of hemophilia A 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous murine studies have demonstrated that neonatal IV administration of AAV results in high early expression in the liver and lower expression in myocytes 15 . With hepatic proliferation, substantial loss of expression occurs in the rapidly developing neonatal mouse liver 15, 18, 33 . Prior studies by Wilson et al with AAV8-mediated transduction in one-week-old rhesus monkeys were found to be safe and to produce high hepatic GFP transduction using the liver-specific promoter thyroxine binding globulin 35 .…”
Section: Resultsmentioning
confidence: 99%